2013
DOI: 10.1590/s1516-635x2013000300002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of side-curtain color on broiler chick behavior

Abstract: Brazilian poultry production is prospering, and negative-pressure broiler houses are increasingly used to improve environmental control. One important issue is the color of the side curtains used in such houses due to the influence of colors on broiler behavior. This study aimed at evaluating the influence of different curtain color on the welfare of 7-day-old broilers, considering luminosity and other environmental parameters. Chicks were housed in three different negative-pressure broiler houses either with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…Os aviários foram equipados com forro e cortinas laterais de lona na cor azul (Abreu, Abreu, Coldebella, Jaenisch & Paiva, 2007;Vercellino et al, 2013), lâmpadas de aquecimento e iluminação, bebedouros, comedouros, cama de frango (palha de arroz), quadros de comando e acionamento dos sistemas elétricos (iluminação, climatizadores, sistema de refrigeração e bombas d'água).…”
Section: Metodologiaunclassified
“…Os aviários foram equipados com forro e cortinas laterais de lona na cor azul (Abreu, Abreu, Coldebella, Jaenisch & Paiva, 2007;Vercellino et al, 2013), lâmpadas de aquecimento e iluminação, bebedouros, comedouros, cama de frango (palha de arroz), quadros de comando e acionamento dos sistemas elétricos (iluminação, climatizadores, sistema de refrigeração e bombas d'água).…”
Section: Metodologiaunclassified
“…The brightness of the environment has been proven to affect behavior, physiology, and welfare of broiler house (Classen et al, 2004;Rutz, & Bermudez, 2004;Olanrewaju et al, 2006;Kristensen et al, 2007;Lewis et al, 2007;Castellini et al, 2012;Deep et al, 2012;González-Garcia et al, 2014). These birds are kept in rooms with artificial lighting that differs from natural daylight in terms of color, intensity and photoperiod (Gou & Cherry, 2004;Lewis et al, 2004;Alvino et al, 2009) and intermittency (Vercellino, 2013). Cao et al (2008) and Mendes et al (2010) have shown that light intensity does affect the performance of the broiler.…”
Section: Introductionmentioning
confidence: 99%
“…Broiler strains have fast growth and high genetic potential, but adequate conditions should be provided for birds to express this potential and achieve satisfactory productive performance (Vercellino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%